IMPROVE YIELD AND DOWNY MILDEW RESISTANCE OF F1 MADURA MAIZE HYBRIDS - Achmad Amzeri; Kaswan Badami (Indonesian Agency for Agricultural Research and Development, 2020)
Maize production in Madura Island is low. The study aimed to evaluate the agronomic performances (flowering age, harvesting age, and yield), heterosis effect, and resistance to downy mildew disease of F1 Madura maize hybrids. Ten F1 maize hybrids and seven respective parents were evaluated at the experimental center of the Agro-Technology Study Program of Agriculture Faculty, the University of Trunojoyo Madura, from July to December 2017. The experiments were arranged in a randomized block design, three replications, with a 50–100 plant population per unit. The parents were T12, T16, G10, G14, E02, Td04 and L1 genotypes having resistance to downy mildew (Peronosclerospora maydis). The results showed that the flowering age of the F1 Madura maize hybrids ranged 35–39 days, the harvesting age was 74–81 days, and the yield ranged from 2.90–6.40 t ha-1. Three hybrids showed the highest yield (T12 x L1 = 6.40 t ha-1, T16 x L1 = 5.42 t ha-1, and E02 x L1 = 5.90 t ha-1), and resistance to downy mildew, i.e. T12 x L1 (26.67%), T16 x L1 (26.67%), and E02 x L1 (26.67%). Two hybrids showed the highest heterosis values for yield, i.e. T12 x L1 (65.80%) and E02 x L1 (54.65%). The study suggests that three F1 Madura maize hybrids (T12 x L1, T16 x L1 and E02 x L1) are prospective to be developed further for high yield and resistance to downy mildew.